2006
DOI: 10.1353/mcb.2006.0029
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation, Consolidation, and Efficiency: Evidence from the Spanish Insurance Industry

Abstract: This paper provides new information on the effects of deregulation and consolidation in financial services markets by analyzing the Spanish insurance industry. The sample period 1989-98 spans the introduction of the European Union's (EU) Third Generation Insurance Directives, which deregulated the EU insurance market. Deregulation has led to dramatic changes in the Spanish insurance market; the number of firms declined by 35%, average firm size increased by 275%, and unit prices declined significantly in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
143
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 33 publications
13
143
0
9
Order By: Relevance
“…Previous research into non-life insurance revealed substantial scale economies averaging above 10% for the Dutch market (Bikker and Gorter, 2011). Similar results were found in studies focusing on the US and several European countries (Cummins and Weiss, 2014;Kasman and Turgutlu, 2009;Fenn et al, 2008;Cummins and Rubio-Misas, 2006;Fecher et al, 1991). This paper contributes to the literature by applying the PCS measure of competition, which has to date been rarely used.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous research into non-life insurance revealed substantial scale economies averaging above 10% for the Dutch market (Bikker and Gorter, 2011). Similar results were found in studies focusing on the US and several European countries (Cummins and Weiss, 2014;Kasman and Turgutlu, 2009;Fenn et al, 2008;Cummins and Rubio-Misas, 2006;Fecher et al, 1991). This paper contributes to the literature by applying the PCS measure of competition, which has to date been rarely used.…”
Section: Introductionsupporting
confidence: 79%
“…Their results show that cost efficiency is 39% for non-life insurance when using the DEA methodology and no less than 74% when using SFA. According to Cummins and Rubio-Misas (2006), cost efficiency for Spanish insurers is relatively low, with estimates from 1998 averaging 30%, obtained using the DEA methodology. As the methodologies and approaches differ, efficiency levels cannot always be compared.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Cummins, Weiss and Zi (1999) have analysed the efficiency of U.S. mutual and stock property-liability insurers using frontier analysis while Cummins and Rubio-Misas (2001) on the sample of Spanish firms have used frontier efficiency analysis to estimate cost, technical, and allocative efficiency, as well as using Malmquist analysis to measure total factor productivity (TFP) change. Fecher et al (1993) investigated the relative productive performance or technical efficiency of French insurance companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As stated by BeckerBlease et al (2010), in addition to number of employees, total assets and sales are alternative measures of firm size. However, due to the unique features and business activities of insurance companies in relation to other companies, the authors have decided to use gross written premium as the basis for calculating the size of an insurance company following Cummins and Rubio-Misas (2001) approach. This variable (ln_SIZE) is calculated as a natural logarithm of total gross written premium.…”
Section: Variables Descriptionmentioning
confidence: 99%
“…Consistent with the recent literature, we use the modified version of the value-added approach to measure the insurers' outputs and inputs (See [5,[16][17][18][19][20][21]). Based on the above-mentioned authors we can say that there are three principal services, including the risk-pooling and risk-bearing, the real financial services related to insured losses, and intermediation are provided by insurance firms.…”
Section: Dataset and Variables Definitionmentioning
confidence: 99%